2016
DOI: 10.1180/minmag.2016.080.062
|View full text |Cite
|
Sign up to set email alerts
|

Reaction aureoles around uraninites within biotite and plagioclase: evidence of low-temperature sequential fluid alteration andLREE-mobilization from monazite

Abstract: Optical microscopy, Raman spectroscopy and electron probe microanalyses were conducted on a migmatitic metapelite to investigate the effects of alpha radiation and subsequent alteration at the interface between uraninite inclusions and the host minerals biotite, chlorite and albitic plagioclase. The study reveals (1) anomalous colouration under the polarizing microscope; (2) pertinent changes in the characteristic Raman spectra of host phases; (3) reaction aureoles, composed of secondary phases (viz. chlorite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…These changes took place under low-temperature (≤150°C) conditions, wherein radial cracks (within plagioclase) and cleavages/fractures (within biotite) favored fluid infiltration-circulation into the reaction aureoles. Decrease in the LREEs from the matrix monazites and their enrichment as a discrete LREE phase within the damaged aureoles in plagioclase demonstrate micrometer-scale LREE mobility (Ozha et al, 2016). EPMA dating of uraninite from the Samarkiya area, central Rajasthan reveals three distinct ages.…”
Section: Uranium Ree Nb Ta W Oresmentioning
confidence: 89%
“…These changes took place under low-temperature (≤150°C) conditions, wherein radial cracks (within plagioclase) and cleavages/fractures (within biotite) favored fluid infiltration-circulation into the reaction aureoles. Decrease in the LREEs from the matrix monazites and their enrichment as a discrete LREE phase within the damaged aureoles in plagioclase demonstrate micrometer-scale LREE mobility (Ozha et al, 2016). EPMA dating of uraninite from the Samarkiya area, central Rajasthan reveals three distinct ages.…”
Section: Uranium Ree Nb Ta W Oresmentioning
confidence: 89%
“…Then, the uraninite crystals underwent various degrees of post-crystallization alteration, which is demonstrated by the variable, low to high Si contents (0.43-12.84 wt.% SiO 2 ) in altered uraninite [16]. Furthermore, alteration of natural uraninite is an integrated product of self metamictization and hydrothermal overprinting events, which are characterized by the incorporation of impurities (e.g., Ca, Fe and Si), the depletion of Pb and U and the generation of a series of secondary minerals (e.g., coffinite, hematite, chlorite and clay minerals [21,73]). Here, the progressive development of radial microfractures through time, from the uraninite grains spreading out into the surrounding rock-forming minerals, combined with amorphization of the uraninite structure during metamictization facilitated the fluid-rock chemical exchange of elements (e.g., Zhang et al [73]; Bonnetti et al [74]) during the successive episodes of hydrothermal alteration proposed in Section 5.1.…”
Section: Processes Responsible For Uraninite Alteration and Radiohalo Formationmentioning
confidence: 99%
“…Previous studies have demonstrated that the post-irradiation fluid-assisted alteration of natural uraninite and their related secondary phases in "radiohalos" provide a good opportunity to study the remobilization of dissolved elements (including REEs and U) in uraninite, the nature of hydrothermal fluids and the resistance of host minerals for containment of radioactive waste [17][18][19][20]. For example, differential microscale hydrothermal mobility of Pb and U within one single uraninite crystal was measured from the Cigar Lake uranium deposit, Canada [16], and radiohalos composed of chlorite and K-feldspar around uraninite from the Mangalwar complex, India, were interpreted to form under low-temperature, K-rich fluid conditions [21]. However, few nano-scale works ( [16] and references therein) have been done to evaluate the redistribution of elements liberated from uraninite and characterize the nature of fluids that were involved during the post-crystallization stage.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary silicate minerals included chlorite, hydromica and other clay minerals (Fig.2 a, f, i&j, all labeled by Chl.). Haloes of secondary phase at interface between uraninite grains within host mineral been reported by Rimsaite, Ozha Seydoux-Guillaume and Prochazka [9][10][11][12] . Host minerals include biotite from granites associated with uranium deposits [9] , diopside and calcite [10] , quartz, albite, K-feldspar, and cordierite [11] , biotite and plagioclase [12] in metamorphic rocks.…”
Section: Hydrothermal Alteration Around Uraninitementioning
confidence: 99%